An Examination of Racial and Ethnic Variation in the Effect of Prison Visitation on Recidivism - Dismuke, Raven C. (Crime & delinquency, 2024)
Over the past decade, a growing number of scholars have explored the effect of prison visitation on individuals? post-release behavior. Findings from this work generally indicate a link between in-prison visits and reductions in recidivism. Yet whether the effect of visitation on recidivism operates similarly across race and ethnicity remains largely unexplored. In the current investigation, we draw on data from the Florida prison system, to examine associations between visitation and recidivism, including whether the effect of visitation is similar across race and ethnic groups. Our findings contribute to research and theorizing on prison visitation by further unpacking the visitation-recidivism link. We conclude by discussing the broader policy implications of our findings.